Shedding of TNF receptor 2 by effector CD8+ T cells by ADAM17 is important for regulating TNF‐α availability during influenza infection. Issue 3 (27th May 2015) - DeBerge, Matthew P.; Ely, Kenneth H.; Wright, Peter F.; Thorp, Edward B.; Enelow, Richard I.
Abstract : Soluble TNFR2 production during influenza infection, with emphasis on CD8 + T cells. Abstract : Elevated levels of solTNFR2 are observed in a variety of human pathophysiological conditions but regulation of TNFR2 levels during disease is not well understood. We found that solTNFR2 levels were increased following influenza infection or live‐attenuated influenza virus challenge in mice and humans, respectively. As influenza‐specific CD8 + T cells up‐regulated expression of TNFR2 after infection in mice, we hypothesized that CD8 + T cells contributed, in part, to solTNFR2 production after influenza infection and were interested in the mechanisms by which CD8 + T cells regulate TNFR2 shedding. Activation of these cells by TCR stimulation resulted in enhanced shedding of TNFR2 that required actin remodeling and lipid raft formation and was dependent on MAPK/ERK signaling. Furthermore, we identified ADAM17 as the protease responsible for TNFR2 shedding by CD8 + T cells, with ADAM17 and TNFR2 required in "cis" for shedding to occur. We observed similar activation thresholds for TNF‐α expression and TNFR2 shedding, suggesting that solTNFR2 functioned, in part, to regulate solTNF‐α levels. Production of solTNFR2 by activated CD8 + T cells reduced the availability of solTNF‐α released by these cells, and TNFR2 blockade during influenza infection in mice enhanced the levels of solTNF‐α, supporting this hypothesis. Taken together, this study identifies critical cellular mechanisms regulating TNFR2 shedding on CD8 + T cells and demonstrates that TNFR2 contributes, in part, to the regulation of TNF‐α levels during infection.